OTOMATISASI PENGATURAN PH DAN TDS PADA HIDROPONIK NFT MENGGUNAKAN MIKROKONTROLER ESP32 DAN LOGIKA FUZZY - Muhammad Santriko; Agung Kridoyono; Mochamad Sidqon; Anton Breva Yunanda; Istantyo Yuwono (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Hydroponic systems require precise control over nutrient levels and water flow to ensure optimal plant growth. Manual management is still widely used, which often leads to imprecise nutrient delivery, water wastage, and inefficiency. This study aims to develop an intelligent system based on the Internet of Things (IoT) and fuzzy logic to automatically regulate pH and TDS levels in a Nutrient Film Technique (NFT) hydroponic setup. The methodology includes the integration of pH, TDS, ultrasonic, and flow sensors with an ESP32 microcontroller and the Blynk application. Sensor data is processed using fuzzy logic to produce outputs in the form of liquid volume (liters) and pump activation duration (seconds). The system is designed to control pH UP/DOWN and fertilizer pumps are automatically based on the delta and error values of the measured parameters. Implementation results indicate that the system effectively maintains nutrient stability and reduces water and fertilizer wastage. Additionally, it enables real-time remote monitoring via a mobile application. Therefore, this intelligent system offers an efficient and adaptive solution for supporting sustainable hydroponic farming.